"Stand back, " said the elephant, "I'm going to sneeze!" - Thomas, Patricia, 1934-2021.; Tripp, Wallace (New York : Lothrop, Lee & Shepard Books, 1990)
Knowing the havoc it will cause, all the animals try to prevent the elephant from sneezing.
Keywords: Stories in rhyme; Animals -- Fiction